Qatar : 2010 Article IV Consultation-Staff Report; Staff Statement and Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Qatar. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Qatar has weathered the global economic crisis well. Enhancement of liquefied natural gas capacity (LNG), government support to the banking system, and increase in public spending sustain the high growth rates. There is a need to monitor aggregate demand to prevent the resurgence of inflation pressures. The creation of a financial stability unit and the results of recent stress tests show the banking system's resilience to market and credit risks. The coordination among data providers and intention to seek technical assistance in consumer price index are noted.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet